The Temporal and Spatial Characteristics and Influencing Factors of Low-Carbon Economy Efficiency and Science and Technology Development Level in China’s Provinces From the Perspective of Uncoordinated Coupling - Guangming, Yang; Qingqing, Gui; Fengtai, Zhang; Guofang, Gong; Yunrui, Yang (Frontiers in Environmental Science, 2022)
The development of a low-carbon economy has become a global problem. In order to achieve sustainable development in China, low-carbon economic efficiency(LCEE) is particularly important. Therefore, this study presents a comprehensive LCEE index of China's provinces and evaluates the LCEE of 30 provinces in China from 2008 to 2017. Based on the uncoordinated coupling model, this study discusses the interaction between the provincial LCEE and the level of scientific and technological development (STDL) in China. The panel VAR model is used to evaluate the interactive relationship between the development of LCEE and the STDL in China. The tobit model is used to analyze the factors influencing the uncoordinated coupling degree (UCCD). The main conclusions are as follows: (1) during the study period, the STDL and LCEE indices of 30 provinces in China showed an increasing trend, and the development level of the eastern region was higher than that of the western region. (2) During the study period, the UCCD of the provinces showed an overall decreasing trend. Spatially, UCCD values lower than 0.5 were mainly concentrated in the eastern and southern provinces, and gradually spread to the north. (3) The UCCD of the provinces show positive spatial autocorrelation, and the spatial accumulation effect is significant. (4) Each province's STDL and LCEE values have positive progressive effects and inertia development characteristics, and their influences are gradually declining. The STDL has a positive promotion effect on the LCEE, but the mechanism is not obvious. (5) Patent authorization, urbanization level, transportation level, and financial development scale have negative impacts on the UCCD between the LCEE and the STDL. Therefore, it is necessary to emphasize the coordinated development of a low-carbon economy and STDL by promoting the development of a low-carbon economy through scientific innovation.